2016
DOI: 10.1002/jcp.25364
|View full text |Cite
|
Sign up to set email alerts
|

MMP-8 Is Critical for Dexamethasone Therapy in Alkali-Burned Corneas Under Dry Eye Conditions

Abstract: Our previous studies have shown that Dexamethasone (Dex) reduced the expression of matrix-metalloproteinases (MMPs -1,-3,-9,-13), IL-1β and IL-6, while it significantly increased MMP-8 mRNA transcripts in a concomitant dry eye and corneal alkali burn murine model (CM). To investigate if MMP-8 induction is responsible for some of the protective effects of Dex in CM, MMP-8 knock out mice (MMP-8KO) were subjected to the CM for 2 or 5 days and topically treated either with 2 μl of 0.1% Dexamethasone (Dex), or sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…98 Studies with gene KO and pharmacologic inhibitors showed that part of the beneficial effects from dexamethasone in this model were through an increase in MMP-8. 84 Nonpreserved topical methylprednisolone administered three to four times per day significantly improved signs and symptoms of dry eye in patients with SS. 109 Clinically, prolonged use of topical corticosteroids is plagued by frequent side effects, such as cataract induction and glaucoma, that limit their wide use in dry eye; 109 however, the introduction of "soft-steroids" that carry a markedly reduced risk of sightthreatening side effects has led to community acceptance of corticosteroid therapy on a limited basis.…”
Section: Corticosteroidsmentioning
confidence: 90%
See 1 more Smart Citation
“…98 Studies with gene KO and pharmacologic inhibitors showed that part of the beneficial effects from dexamethasone in this model were through an increase in MMP-8. 84 Nonpreserved topical methylprednisolone administered three to four times per day significantly improved signs and symptoms of dry eye in patients with SS. 109 Clinically, prolonged use of topical corticosteroids is plagued by frequent side effects, such as cataract induction and glaucoma, that limit their wide use in dry eye; 109 however, the introduction of "soft-steroids" that carry a markedly reduced risk of sightthreatening side effects has led to community acceptance of corticosteroid therapy on a limited basis.…”
Section: Corticosteroidsmentioning
confidence: 90%
“…[82][83][84][85] This simulated the most severe burn cases, where extensive facial and eyelid thermal injury results in eye exposure and desiccation due to loss of protection from the eyelids and reduced blinking. We found there was an additive pathogenic effect of dry eye to alkali burn, with amplification of MMP-3, -8, -9 and -12, IL-6 and IL-1β mRNA expression and sterile corneal perforation in ~30% of animals subjected to the chemical burn and desiccating conditions.…”
mentioning
confidence: 99%
“…MMP functioning in processes of normal and pathological wound healing is currently under active research [9,10]. We determined the MMP-1, MMP-2, MMP-3, MMP-8 and MMP-9 content in the esophageal mucosal (Table 1) and serum (Table 2) of rats after the esophagus 2 nd degree acid burn simulation.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of MMP and TIMP proteins is tightly regulated to maintain adequate balance between ECM synthesis and degradation, which is essential for healthy tissues. Disorders in the regulation of the MMP/TIMP complex have been implicated in many pathological conditions including cancer, Alzheimer’s, cardiovascular or rheumatologic diseases [ 89 , 90 , 91 ], as well as eye diseases such as retinal dystrophies [ 92 , 93 , 94 ], retinal detachment [ 95 ] and proliferative vitreoretinopathy (PVR) [ 49 , 96 , 97 , 98 ], wound corneal healing [ 99 , 100 , 101 ], glaucoma [ 102 , 103 , 104 , 105 ], diabetic retinopathy (DR) [ 106 , 107 , 108 , 109 , 110 ], ocular tumors [ 111 , 112 , 113 , 114 ], pseudoexfoliation syndrome [ 115 , 116 , 117 ], and epiretinal membranes formation [ 118 ]. It is thought that the lack of stability in the regulation of MMPs may play a key role in the pathogenesis of AMD [ 5 , 17 , 50 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ].…”
Section: Extracellular Matrix In the Eye And The Metalloproteinasementioning
confidence: 99%